Dimensional stability and mechanical performance evolution of continuous carbon fiber reinforced polyamide 6 composites under hygrothermal environment - Lei, Yongpeng; Zhang, Tao; Zhang, Jifeng; Zhang, Boming (Journal of materials research and technology, 2021)
This study aimed to investigate moisture absorption behaviors, dimensional stability, and mechanical performance evolution of continuous carbon fibers reinforced with polyamide 6 composites (CF/PA6) under a hygrothermal environment. 3D Fickian model determined the principal three-dimensional (3D) diffusion coefficients by using an optimization algorithm. Three-dimensional changes of samples were measured to quantify the relationship between swelling coefficient and water content. After hygrothermal aging, the tensile properties of PA6 resin and CF/PA6 composites in the transverse direction decreased significantly, but the longitudinal tensile properties of CF/PA6 composites were insensitive to hygrothermal aging. DMA (Dynamic Mechanical Analysis), SEM (Scanning Electron Microscopy) and FTIR (Fourier Transform Infrared) tests were also applied to analyze the mechanism of mechanical properties degradation.